Relationship Between Disc Geometry and Draft Requirement - Yadav, B K; Mani, Indra; Panwar, J S (Journal of Agricultural Engineering, 2006)
A disc is considered as part of shell of a hallow sphere and used as soil working tool with tillage implement. Detailed information about the effect of disc geometry specially disc diameter with varying concavity is not available .A single disc tool carrier was designed to mount and test the performance of disc of different diameter and concavity. A total of nine discs in the diameter range of 510-610 mm and concavity within 51-95 mm were tested under field conditions for their draft requirement and work performance .The results showed that draft increased consistently with increase in diameter of the disc but the range of variation was low. The draft range in unploughed soil for 510, 560 and 610 mm disc was observed as 177-194, 192-204 and 176-227 kg respectively. The increase in draft for higher diameter disc was mainly due to increase in width of cut. Disc concavity showed a pronounced effect on draft. Over the three levels of diameter, the concavity variation of 17,14 and 19mm caused draft variations of 14, 18 and 43 kg, respectively, in the same order.